2015
DOI: 10.3126/ijasbt.v3i1.12014
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Rice Varieties against Brown Leaf Spot Disease at Jyotinagar, Chitwan, Nepal

Abstract: A field experiment was conducted on fourteen rice varieties to determine the level of resistance against brown leaf spot (Bipolaris oryzae)disease at Karma Research and Development Center, Jyotinagar, Chitwan during summer in 2013. Design used was randomized completeblock design with three replications. Disease severity, total AUDPC value, thousand grain weight and grain yield were highly significant amongthe rice varieties. Disease severity and total AUDPC value ranged from 21.73% to 58.07% and 614.8 to 1827 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
3
5
0
Order By: Relevance
“…The present study results demonstrated varying responses of pigmented upland rice cultivars to brown leaf spot. Similar results have previously been observed in white-lowland rice by several studies (Percich et al1997;Hossain and Kulkarni 2001;Magar 2015;Pantha et al 2017). Using the same disease severity rating scale (IRRI 2002), the disease severity (11.11-40.70%) and total AUDPC (398.42-1081.30%-days) ranges of the present study were a bit lower than that observed by Magar (2015), who recorded disease severity and AUDPC value ranges of, respectively, 21.73-58.07% and 614.8-1827%-days.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The present study results demonstrated varying responses of pigmented upland rice cultivars to brown leaf spot. Similar results have previously been observed in white-lowland rice by several studies (Percich et al1997;Hossain and Kulkarni 2001;Magar 2015;Pantha et al 2017). Using the same disease severity rating scale (IRRI 2002), the disease severity (11.11-40.70%) and total AUDPC (398.42-1081.30%-days) ranges of the present study were a bit lower than that observed by Magar (2015), who recorded disease severity and AUDPC value ranges of, respectively, 21.73-58.07% and 614.8-1827%-days.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results have previously been observed in white-lowland rice by several studies (Percich et al1997;Hossain and Kulkarni 2001;Magar 2015;Pantha et al 2017). Using the same disease severity rating scale (IRRI 2002), the disease severity (11.11-40.70%) and total AUDPC (398.42-1081.30%-days) ranges of the present study were a bit lower than that observed by Magar (2015), who recorded disease severity and AUDPC value ranges of, respectively, 21.73-58.07% and 614.8-1827%-days. These differences presumably occurred due to different rice genotypes being tested (24 genotypes in this study and 14 genotypes in the study by Magar (2015) In addition to genotypic differences, the difference in total AUDPC might have happened due to difference in number of disease assessments carried out as total AUDPC is the accumulation of all the recorded disease severity during the experimental period.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It is also observed previously paddy variety differ in utilization of silicon from the soil. (Ma et al, 2007;Sahebi et al, 2017), and varietal difference were also observed in the incidence of brown spot disease Magar (2015), varieties like Kala Namak, Ganga Kaveri, are tall in height and very much prone to the lodging, which may be due to deficiency of Silicon in the soil and deferential ability of genotype of paddy to uptake silicon. Varieties like Kala Namak Dwarf, NP 360, Shri Ram 502, NDR3112.NDR 359 and NDR 2064, have shown partial resistance to the disease may be up taking Si in some amount which is in support of work done by (Idris et al, 1975;Majumadar et al, 1985).…”
Section: Area Under Disease Progress Curvementioning
confidence: 98%